Organic Food Processing: A Review (International Journal of Innovative Research in Engineering & Management, 2023)
Organic farming and food production is a  broad approach to farm management and food production  that aims for long-term sustainability, high-quality  products, and the use of techniques that do not affect the  environment, human, plant, or animal health and welfare Any technology that does not convert modern foods into  food products is referred to as a food process. This might  include laundering, chopping, pasteurizing, freezing,  fermentation, packing, state transition, and a whole lot  more. Adding substances to food, for example, to extend  the cooking time, is also part of the culinary process. In  addition to contributing in environmental defense and  preservation by increasing yields and reducing reliance on  chemical pesticides and herbicides, genetically modified  crops are expected to address a variety of hunger and  deficiency disease concerns throughout the world. Though  organic food products have the healthiest composition, they  come with their own set of drawbacks. However, they are  the most popular to eat due to their superior natural  composition. The different methods involved in the organic  food processing maintain the integrity of organic food  products even after they reach home factories to be  processed and distributed to customers for consumption.
Keywords: Agriculture; Disease; Management; Organic; Pesticides